2018
DOI: 10.5194/amt-11-3955-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparing OMI-based and EPA AQS in situ NO<sub>2</sub> trends: towards understanding surface NO<sub><i>x</i></sub> emission changes

Abstract: Abstract. With the improved spatial resolution of the Ozone Monitoring Instrument (OMI) over earlier instruments and more than 10 years of service, tropospheric NO 2 retrievals from OMI have led to many influential studies on the relationships between socioeconomic activities and NO x emissions. Previous studies have shown that the OMI NO 2 data show different relative trends compared to in situ measurements. However, the sources of the discrepancies need further investigations. This study focuses on how to ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 75 publications
0
42
1
Order By: Relevance
“…Xu et al (2013) reported that this ratio varied in different seasons and locations. Hence, the applied correction ratios by Zhang et al (2018) may not be representative for the different campaigns in this study. By using a consistent NO 2 dataset, the R 2 between the unknown HONO source and the product of SWR×NO 2 ×aerosol surface area was the highest when compared to other correlations in Liu et al (2014).…”
Section: Unknown Hono Source Estimationmentioning
confidence: 96%
See 1 more Smart Citation
“…Xu et al (2013) reported that this ratio varied in different seasons and locations. Hence, the applied correction ratios by Zhang et al (2018) may not be representative for the different campaigns in this study. By using a consistent NO 2 dataset, the R 2 between the unknown HONO source and the product of SWR×NO 2 ×aerosol surface area was the highest when compared to other correlations in Liu et al (2014).…”
Section: Unknown Hono Source Estimationmentioning
confidence: 96%
“…PAN). We further applied the observed seasonal ratios of coincident NO 2 measurements of by the chemiluminescence instrument to the more selective photolytic instrument reported by Zhang et al (2018) to correct the NO 2 data and found that the R 2 (0.87) increased after the correction (figure 2(f)). Xu et al (2013) reported that this ratio varied in different seasons and locations.…”
Section: Unknown Hono Source Estimationmentioning
confidence: 99%
“…For more consistent trend analysis, the observed pixels were considered only for the rows 6-23 because of the known row anomaly issue [35,43]. Besides, the observed pixels contaminated by bright surface albedo (larger than 0.3) and clouds (cloud radiance fraction larger than 50%) were not involved in the analysis [38].…”
Section: Omi Retrieved No 2 Columnsmentioning
confidence: 99%
“…The uncertainty in the tropospheric NO2 columns from the DOMINO v2.0 algorithm, caused mainly by the AMF calculation was 1.0 × 10 15 molecules cm −2 with a relative error of 25% [38]. For more consistent trend analysis, the observed pixels were considered only for the rows 6-23 because of the known row anomaly issue [35,43]. Besides, the observed pixels contaminated by bright surface albedo (larger than 0.3) and clouds (cloud radiance fraction larger than 50%) were not involved in the analysis [38].…”
Section: Target Areasmentioning
confidence: 99%
“…2 Model and data description 2.1 REAM REAM has been applied and evaluated in many research applications including ozone simulation and forecast, emission inversion and evaluations, and mechanistic studies of chemical and physical processes (Alkuwari et al, 2013;Cheng et al, 2017Cheng et al, , 2018Choi et al, 2008a, b;Gu et al, 2013Gu et al, , 2014Koo et al, 2012;Liu et al, 2012Liu et al, , 2014Wang et al, 2007;Yang et al, 2011;Zhang et al, 2017Zhang et al, , 2018Zhang and Wang, 2016;Zhao and Wang, 2009;Zhao et al, 2009aZhao et al, , 2010. REAM as used in this work, the model domain of which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%